Synthesis of Diaza[5]helicenes by ortho,ortho′-Fusion of ortho-Terphenyls - Herzog, Stefan; Marten, Inka; Weiß, Aaron; Podlech, Joachim (Synthesis, 2022)
Double ortho-fusion in suitably substituted ortho-terphenyls was used for the synthesis of diaza[5]helicenes. Bis(carboxamido)-substituted ortho-terphenyls can be condensed to 5,9- and 6,9-diaza[5]helicenes, where substituents at the 6,10- and 5,10-positions, respectively, are introduced with the carboxamido groups. While a twofold coupling sequence with intermediate protection of one amino group has to be used for 5,9-diaza[5]helicenes, a more concise sequence avoiding the protection leads to 6,9-diaza[5]helicenes. The simple heating of ortho,ortho′-diazidoterphenyls furnishes 5,8-dihydroindolo[2,3-c]carbazoles, i.e., [5]helicenes with alternating benzene and pyrrole rings.
Keywords: helicenes; terphenyls; cross-coupling; Suzuki coupling; aromatic compounds; boronates; amides; azides